Evaluation of Waste Management Through the Lens of Public Service Management: A Literature-Based Study in Tasikmalaya City - Yanti Heryanti (Publica: Jurnal Pemikiran Administrasi Negara, 2025)
Waste management in Tasikmalaya City still faces serious challenges, especially in urban centers, and has not yet shown optimal effectiveness as part of public services. This problem encompasses the entire management chain, from collection and transportation to final processing. A comprehensive literature study identified significant weaknesses in public service management as the root cause. Although efforts have been made, the results indicate that the existing system has not been able to meet public expectations for a clean and healthy environment. The limited availability of infrastructure is one of the main obstacles to effective waste management. The lack of adequate infrastructure and waste management facilities, such as representative temporary waste disposal sites (TPS), sufficient transport fleets, and modern waste processing technology, significantly hinders the process. Furthermore, weak coordination among related agencies exacerbates the situation, leading to overlapping authorities and a lack of synergy in policy implementation. These factors collectively contribute to the ineffective waste handling in Tasikmalaya City. On the other hand, low public awareness and active participation are also significant impediments. The lack of widespread and continuous socialization regarding the importance of waste sorting at the source, collection schedules, and the negative impact of waste on the environment makes people reluctant to get involved. This is evident from the still prevalent practice of people littering or not sorting their waste, adding to the burden on an already limited management system. Increasing public awareness is key to creating a cleaner environment. To overcome these problems, fundamental reforms in public service management within Tasikmalaya City's waste management sector are urgently needed. This includes strengthening human resource capacity, reinforcing regulations and stricter law enforcement, and more innovative strategies to increase public participation and awareness. With a combination of these efforts, it is hoped that a more sustainable, effective waste management system can be created, capable of providing optimal services to the community, thereby making Tasikmalaya a clean and comfortable city.